Child rearing practices and attitudes of adolescent fathers - Lalonde, Simon (1988)
There has been considerable interest and sometimes concern for teenage parents. This interest has developed for two reasons, firstly, it has been viewed that teenage parents are inappropriately young to have children, and secondly, it has popularly been thought that the number of female teenagers becoming pregnant and subsequently giving birth to children has dramatically increased over the last twenty years. Much of this attention has focused on the young mother, because she has been thought to shoulder the major responsibility for looking after the child. This is not untypical of research on parenting which has adopted a mother biased approach, although there has been a more recent interest in the fathers. The object of this study was to examine the experiences of one hundred young fathers, aged seventeen to twenty two, who were regularly involved with their infant. The fathers were interviewed at home and data was collected on all aspects of their family participation.